Online preconcentration of arsenic compounds by dynamic pH junction-capillary electrophoresis - Jaafar, Jafariah (Wiley Interscience, 2007)
An online preconcentration technique by dynamic pH junction was studied to improve the detection limit for anionic arsenic compounds by CE. The main target compound is roxarsone, or 3-nitro-4-hydroxyphenylarsonic acid, which is being used as an animal feed additive. The other inorganic and organoarsenic compounds studied are the possible biotransformation products of roxarsone. The arsenic species were separated by a dynamic pH junction in a fused-silica capillary using 15 mM phosphate buffer (pH 10.6) as the BGE and 15 mM acetic acid as the sample matrix. CE with UV detection was monitored at a wavelength of 192 nm. The influence of buffer pH and concentration on dynamic pH junction were investigated. The arsenic species focusing resulted in LOD improvement by a factor of 100– 800. The combined use of C18 and anion exchange SPE and dynamic pH junction to CE analysis of chicken litter and soils helps to increase the detection sensitivity. Recoveries of spiked samples ranged between 70 and 72%.